0078 Clinical Simulation As A Tool For Professional Decision Making. (1st November 2014) - Foreman, David
Abstract : Background/context: Having worked in an environment where 'high-tech' simulation was used frequently and effectively to teach clinical/procedural skills, and having seen it used effectively to promote the recognition of the impact of human factors in healthcare settings I am keen to explore the use of simulation to recreate some of the more difficult decisions healthcare professionals have to make. Simulation is currently used in the context of a final year pre-registration nursing course before the students go into their final (management) placement to address some of the clinical and professional dilemmas faced by nursing staff in both acute and non-acute settings. Methodology (used or planned): A mixture of clinical scenarios have been delivered with a range of foci, from the acutely unwell patient who needs ABCDE assessment, to the care of the dying patient who may or may not need decisions making about the course of their death. The students attending this simulation event were questioned anonymously to gauge their perceptions of what they felt were the important take home messages from the simulation experiences. Results/outcomes (anticipated or recorded to date): The students can see the benefits as learners to the use of simulation in both the acute and non-acute care setting. The take home message for those participating in the simulation scenarios is that the majority of the learning takes place in the debrief and not for the person in the simulated environment. And finally, that non-acute scenarios can stimulate as interesting and professionally useful discussions/learning points and more acute scenarios. Potential impact: We hope to use simulation more frequently, more effectively, and in more creative ways across the pre-reg curriculum, therefore increasing the profile and student engagement, thus improving outcomes for acute care, non-acute care and clinical/professional decision making. Reference: NMC (2010) Standards for pre-registration nursing education, NMC Publications, London